Comparison of two telemetric intestinal temperature devices with rectal temperature during exercise - Bogerd, C P; Velt, K B; Annaheim, S; Bongers, C C W G; Eijsvogels, T M H; Daanen, H A M (Physiological measurement, 2018)
The discomfort caused by rectal probes and esophageal probes for the estimation of body core temperature has triggered the development of gastrointestinal (GI) capsules that are easily accepted by athletes and workers due to their non-invasive characteristics. We compare two new GI capsule devices with rectal temperature during cycle ergometer exercise and rest. Eight participants followed a protocol of (i) 30 min exercise with a power output of 130 W, (ii) 5 min rest, (iii) 10 min self-paced maximum exercise, and (iv) 15 min rest. Core temperature was measured using two GI-capsule devices (e-Celsius and myTemp) and rectal temperature. The myTemp system provided only slightly different temperatures to the rectal temperature probe during rest and exercise. However, the factory-calibrated e-Celsius system showed a systematic rectal temperature underestimation of 0.2 °C that is corrected in the 2018 versions. Both GI capsules reacted faster to temperature changes in the body compared to the rectal temperature probe during the rest period following maximum exercise. The GI-capsules react faster to temperature changes in the body compared to the rectal temperature probe, in particular during the rest period following exercise.